Analisis Indikator Berpikir Kritis Terhadap Karakter Rasa Ingin Tahu dalam Kurikulum 2013 - Nurun Ni'mah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The aim of this study is to provide a literature review related to critical thinking indicators that can be used to develop the character of curiosity in the 2013 curriculum. This type of research is library research or literature study. In this study, the data sources were obtained from books, journals, or scientific articles relevant to the selected research topic. The data analysis technique used in this research is the content analysis method. The results of the study show that there are critical thinking indicators that can be used to develop the character of students' curiosity. This can be seen from operational verbs that can be used in critical thinking indicators, including